2010
DOI: 10.1515/hf.2010.084
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the longitudinal modulus of elasticity of Sitka spruce from cellulose orientation and abundance

Abstract: Sitka spruce (Picea sitchensis) is the most widely planted commercial tree species in the United Kingdom and Ireland. Because of the increasing use of this species for construction, the ability to predict wood stiffness is becoming more important. In this paper, a number of models are developed using data on cellulose abundance and orientation obtained from the SilviScan-3 system to predict the longitudinal modulus of elasticity (MOE) of small defect-free specimens. Longitudinal MOE was obtained from both bend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 11 publications
2
18
2
Order By: Relevance
“…This parameter predicted the modulus of elasticity with a linear modeling better than MFA and density alone (non-linear trends). For example, McLean et al (2010) recently demonstrated that 76% of the variation in modulus of elasticity was explained by the factor ρ/MFA in wood samples of Picea. [24,40] for the intercept (R²=0.37, residual standard error = 12 MPa).…”
Section: Correlations Among Wood Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…This parameter predicted the modulus of elasticity with a linear modeling better than MFA and density alone (non-linear trends). For example, McLean et al (2010) recently demonstrated that 76% of the variation in modulus of elasticity was explained by the factor ρ/MFA in wood samples of Picea. [24,40] for the intercept (R²=0.37, residual standard error = 12 MPa).…”
Section: Correlations Among Wood Traitsmentioning
confidence: 99%
“…The methods of sampling preparation and measurement should be taken into account for comparing the relationships concerning the density, the microfibril angle, and the modulus of elasticity reported in the previous studies. For instance, Evans and Ilic (2001), Yang and Evans (2003) and McLean et al (2010) had employed the SilviScan device (Evans et al 1999) to perform multiple measurements to obtain a mean MFA across a small strip cut from the specimen. In this study, the microfibril orientation was not the main effect which explained the variability of modulus of elasticity and modulus of rupture.…”
Section: Correlations Among Wood Traitsmentioning
confidence: 99%
“…In Douglas-fir (Pseudotsuga menziesii), density was the most contributor to MOE and MOR, and MFA was relatively unimportant [4]. In Sitka spruce (Picea sitchensis), both static and dynamic MOE were predicted by MFA and density (R 2 = 0.725 and 0.862 respectively) [5]. From these studies, it was assumed that also in hinoki, variation of mechanical properties would be explained by variation of MFA and density.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical and physio-mechanical properties (mainly stiffness, shrinkage and stability) of wood are determined by the fundamental structure of its cells (Barnett and Bonham 2004;Cave 1969;Harris and Meylan 1965;McLean et al 2010;Wardrop and Preston 1947). Studies in radiata pine (Pinus radiata D. Don) and other softwood species have shown that the two most influential wood properties are basic density and the angle of the cellulose microfibrils (MFA) in the S2 layer of wood cell walls (Cown et al 1999;Donaldson 1997;Wagner et al 2012;Walker and Butterfield 1995;Walker 1996;Xu and Walker 2004).…”
Section: Introductionmentioning
confidence: 99%